Analisis Uraian Tugas Tenaga Administrasi Sekolah Urusan Kurikulum Di Slta Se-Kecamatan Pariaman Timur - Susilawati .; Rusdinal .; Irsyad .; Enceria Damanik (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study was motivated by variations in how School Administrative Staff (TAS) handle curriculum-related tasks across secondary schools (SLTA) in the East Pariaman District. Not all schools have administrative staff dedicated specifically to curriculum administration; consequently, these tasks are carried out through the appointment of existing administrative staff or the formation of working groups based on school needs. This study aims to analyze the job descriptions, implementation bases, challenges, and supporting factors regarding the performance of curriculum-related tasks by School Administrative Staff. This study employs a qualitative approach using a descriptive method. Research informants included the Deputy Principal for Curriculum Affairs and School Administrative Staff from MAN Kota Pariaman, SMKN 1 Pariaman, and SMAN 5 Pariaman. Data were collected through observation, interviews, and documentation, and subsequently analyzed using data reduction, data presentation, and conclusion drawing. Data validity was verified through source, technique, and time triangulation. The results indicate that the execution of curriculum-related tasks by School Administrative Staff varies across schools depending on their specific conditions and needs. SMAN 5 Pariaman has dedicated administrative staff for curriculum affairs, whereas at MAN Kota Pariaman and SMKN 1 Pariaman, these tasks are performed by appointed administrative staff or through a Curriculum Working Group (Pokja). Task execution is guided by formal job descriptions, official decrees on task allocation, curriculum work programs, and leadership directives. Challenges faced include limited administrative personnel, heavy workloads, changes in curriculum policy, and the demands of digital-based administration. Supporting factors include coordination, clear task allocation, human resource competence, and training in curriculum administration.